Peranan Usaha Mikro dalam Meningkatkan Kesejahteraan Keluarga di Desa Tondongkura, Kabupaten Pangkep - Budiawan Budiawan (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2022)
The study aims to determine: 1) the role of micro-businesses of the residents of Tondongkura Village in improving the welfare of their families; 2) Obstacles faced by micro-businesses, especially pre-welfare families. This research already uses a qualitative descriptive approach. The data collection methods used are observation, interview, and documentation techniques. Data processing has used three stages: 1)reduction of the data; 2)display data, and: 3)conclusion drawing/verification. The results showed that micro-businesses run by informants in Tondongkura Village could meet their daily needs, including food, clothing, and board needs, informants had savings and education. In running a micro-business, there are several obstacles faced by informants: 1) namely less business capital; 2)high levels of competition; 3)informants are difficulty dividing time between taking care of family, permanent work, and developing their business; 4)low level of education, and; 5)availability of goods. Informants feel many benefits when running micro-businesses, especially in terms of economics in improving family welfare